Doping og Anti-Doping i Kontekst : En analyse af eliteidrætsudøveres oplevelse af anti-doping policy, betydende faktorer for til- og fravalg af doping, (u)lovlige præstationsfremmende midler, grænser og dilemmaer - Overbye, M. (2013)
This project deal qualitatively and quantitatively with the multiple dimensions of doping and anti-doping policy from the perspectives of elite athletes, for example by exploring how elite athletes of different gender, ages and sports approach legal and illegal Performance-Enhancing Drugs and Methods, athletes` perceptions of the TUE system, the whereabouts system after the one-hour testing slot was introduced and athletes` personal experiences during doping tests. The different questions have all contributed to the overall understanding of legal and illegal PEDM and anti-doping policy and of the challenges faced by policy makers (in legislation and regulation) on the one hand and the experiences, attitudes, trust and strategies of top-level athletes when confronted with new laws and rules on the other. The results of this PhD thesis illustrate several challenges in current anti-doping policy, in particular when it comes to implementing anti-doping measures. Results confirm the ambivalent attitudes towards the system (see Hanstad et al., 2009), which can be described (in a simplified way) as the combination of, on the one hand, great support for anti-doping measures and, on the other hand, unintended consequences when policies are implemented, such as negative experiences in athletes` daily lives or the low level of trust in the harmonization of the WADA Code and the efficacy of anti-doping measures. Furthermore, results indicate that although the preventive effects of doping tests and bans from sport are perceived by the majority of athletes as being deterrents, these are not always regarded as the most effective deterrents. Other factors, e.g. social, emotional, personal, and cultural factors, are also taken into consideration by many athletes, thus suggesting the need to focus also on preventive measures, e.g. by introducing a variety of differentiated education programs. Importantly, the study shows that in a number of questions variations are found among athletes of different gender, ages and/or sports. The results highlight the importance of a differentiated approach to the fight against doping and of considering the importance of the sporting network of athletes, in particular sports doctors and coaches. The findings point to the importance of contextual (cultural) aspects and to the different circumstances and conditions prevailing in various sports disciplines.